MicroRNA-221/222 expression in atherosclerotic coronary artery plaque versus internal mammarian artery and in peripheral blood samples. (3rd October 2018) - Bildirici, Aslıhan Esra; Arslan, Serdal; Özbilüm Şahin, Nil; Berkan, Öcal; Beton, Osman; Yilmaz, Mehmet Birhan
Abstract: Background: Atherosclerosis is a disease of the arterial wall with predilection to some sites on others. MicroRNAs (miRNAs) are a class of the non-coding RNAs regulating the target gene expression at post-transcriptional level. Different miRNAs were found at distinct stages of plaque development and expression of miRNAs' might play an important role in the local behaviour of atherosclerotic plaques. Objective: We aimed to investigate and compare mirR-221/222 expression levels in tissues and in circulation in patients with and without overt atherosclerosis. Methods: RNA was isolated from 40 tissues as 20 tissue samples from coronary artery atherosclerotic plaques (CAAP) and internal mammary arteries (IMA), obtained from same individual) and 80 blood (44 patients with atherosclerosis and 36 healthy subjects) samples. MiR-221/222 expression levels were measured using real time PCR. Results: Expression levels of miR-221 was significantly increased in CAAP compared with completely atherosclerosis-free IMA tissues with a 8.94 times fold-change ( p  = 0.015). The miR-221 expression in tissue samples was significantly different in patients with hypercholesterolemia ( p  = 0.010), hypertension ( p  = 0.018) and family history of CAD ( p  = 0.033) versus not. Expression of miR-222 was not statistically significant between the two tissue samples overall. Conclusions: MiR-221 may be a potential biomarker for local atherosclerotic behavior